2012
DOI: 10.4103/1119-3077.104515
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial sensitivity pattern of organisms causing urinary tract infection in children with sickle cell anemia in Maiduguri, Nigeria

Abstract: Etiological agents of childhood urinary tract infections (UTI) in this environment are resistant to most of the drugs commonly recommended for its treatment. Amoxicillin/clavulanic acid, cefuroxime, and gentamicin, are recommended as first-line drugs for treatment of UTI while awaiting results of culture and sensitivity. Ceftriaxone and ceftazidime should be reserved for case of non response to first-line drugs and severe infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
13
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 16 publications
(25 reference statements)
9
13
3
Order By: Relevance
“…(2013).Ciprofloxacin a quinolone compound which act by inhibiting nucleic acid synthesis can be considered as a drug of choice against bacteria associated with nosocomial infections. The high level of resistance exhibited by the isolates to β lactam antibiotics conform with the work of Nwanko et al (2017) which could be as a result of the production of β lactamase enzyme that render the drugs ineffective (Mava et al,2011). Table 5 revealed that 38 out of 355 isolates were MDR (16% from hospital isolates while 6% from non hospital currency notes P<0.005).…”
Section: Resultssupporting
confidence: 81%
“…(2013).Ciprofloxacin a quinolone compound which act by inhibiting nucleic acid synthesis can be considered as a drug of choice against bacteria associated with nosocomial infections. The high level of resistance exhibited by the isolates to β lactam antibiotics conform with the work of Nwanko et al (2017) which could be as a result of the production of β lactamase enzyme that render the drugs ineffective (Mava et al,2011). Table 5 revealed that 38 out of 355 isolates were MDR (16% from hospital isolates while 6% from non hospital currency notes P<0.005).…”
Section: Resultssupporting
confidence: 81%
“…The flouroquinolones showed better sensitivities against the pathogens as was observed in other studies 6,8,9,11,18,26,27 In Maiduguri, 11 Benin 8 and Ilorin, 18 more than 80% of the E. coli isolates was sensitive to ciprofloxacin. S. aureus was 100% sensitive to this drug in Maiduguri.…”
Section: General Characteristics Of the Study Populationsupporting
confidence: 72%
“…Table 2 shows the distribution of the various isolates according to sex. 7,8,9,11,17,18 . However while E. coli was the most common organism causing UTI in our series as was also reported in Benin 8 and Maiduguri, 9 Klebsiella was the dominant organism isolated in studies in Portharcourt, 5 Ibadan 17 and Abakiliki 7 .…”
Section: General Characteristics Of the Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were similar to those reported by others. 14,15 The explanation for this high sensitivity of this urinary isolates to this drugs in this study may be due to the fact that, in this environment, most parents cannot afford this drug even when prescribed and this may lead to low drug pressure and high sensitivity.…”
Section: Discussionmentioning
confidence: 82%